PENINGKATAN KUALITAS MINYAK GORENG BEKAS DENGAN MENGGUNAKAN ADSORBEN ARANG AKTIF DARI AMPAS TEBU YANG DIAKTIVASI DENGAN NaCL - Octarya, Zona; Fernando, Adhitya (Sistem Informasi, 2016)
This study uses activated carbon from bagasse as adsorbent by 75 mg in 200 grams of used cooking oil. Used oil is cooking oil that has been worn for 10 hours and comes from the restaurant industry. Activated carbon is made from leftover bagasse disposal is carbonized at a temperature of 600 oC for 2 hours and was activated by NaCl and 30 % test quality with iodine adsorption test. The test results of iodine adsorption test on activated carbon bagasse is 795,56 mg g and has met the SNI standard. The results showed that the peroxide used cooking oil, oil despicing results, the results of neutralization and bleaching results using bagasse activated charcoal in a row is 10,12 meq/kg, 8,62 meq/kg, 6,04 meq/kg, and 3,93 meq/kg. While the results of the determination of free fatty acids (FFA) on used cooking oil, despicing results, the results of neutralization and bleaching results using bagasse activated charcoal in a row is 2,4 %, 2,016 %, 0,88 % and 0,49 %. The results of the determination of peroxide and free fatty acids (FFA) has not met the quality standard of cooking oil (SNI), but is able to improve the quality of cooking oil.